2015
DOI: 10.1016/j.ijgo.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of conventional laparoscopic sacrocolpopexy versus robot-assisted laparoscopic sacrocolpopexy

Abstract: The clinical outcomes of prolapse surgery are similar with RALSC and LSC, but RALSC is less efficient in terms of cost and time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…From meta‐analyses of the two small randomised studies (totalling 156 patients) and several non‐randomised studies, the literature suggests that sacrocolpopexy performed via RS is associated with greater post‐operative pain and greater cost, with no significant differences in anatomical outcomes, pelvic floor function, quality of life or peri‐operative adverse events . It is speculated that there is a shorter learning curve for robotic‐assisted sacrocolpopexy, but this has not been proven in randomised trials …”
Section: Sacrocolpopexymentioning
confidence: 99%
“…From meta‐analyses of the two small randomised studies (totalling 156 patients) and several non‐randomised studies, the literature suggests that sacrocolpopexy performed via RS is associated with greater post‐operative pain and greater cost, with no significant differences in anatomical outcomes, pelvic floor function, quality of life or peri‐operative adverse events . It is speculated that there is a shorter learning curve for robotic‐assisted sacrocolpopexy, but this has not been proven in randomised trials …”
Section: Sacrocolpopexymentioning
confidence: 99%
“…The transfusion rate after abdominal sacrocolpopexy has been reported as 2.1% and from 0.5-0.8% after minimally invasive sacrocolpopexy. 12,18,19 A multicenter randomized control trial reported rates of transfusion of 3.7% and 2.2% for uterosacral ligament suspension and sacrospinous ligament fixation, respectively. 13 We found the transfusion rate to be 1.05% for procedures done for prolapse only, reflecting a combination of open, vaginal, and minimally invasive approaches.…”
Section: Commentmentioning
confidence: 99%
“…Recurrance rates ranges from 0 to 14%. At the last year in our centre this procedure is the main option for rectal prolapse treatment [10,11].…”
Section: Discussionmentioning
confidence: 99%